PELATIHAN BUDIDAYA MAGOT - Wulandari, Inayah (Biram Samtani Sains, 2024)
The training on maggot cultivation as an alternative to animal feed in Sambirata Village, Cilongok District, Banyumas Regency, aims to overcome organic waste and provide efficient animal feed. The village faces challenges in waste management, while maggots from the Black Soldier Fly (BSF) offer an effective solution in decomposing organic waste and as a highly nutritious feed. The training methods included lectures, discussions, and hands-on practice that successfully improved the understanding and skills of participants, including fish farmers and local communities. This training shows high enthusiasm and maggot potential in waste and animal feed management, with the hope of improving community welfare and local resource management